Evaluasi Sistem Informasi Admisi Terpadu Dengan Metode EUCS di RSUD Dr. Saiful Anwar Malang - Liza Amalia Putri; Maya Weka Santi; Rossalina Adi Wijayanti (Politeknik Negeri Jember, 2020)
Integrated Admision Information System (SISMIDU) is a system that serves to conduct bed managementdata in RSUD Dr. Saiful Anwar Malang. This system is a supporting facility to know the availability of bedinformation so that it can provide fast service in patients. The implementation of SISMIDU still has someobstacles that the system often encountered error in conducting patient data search, it takes a long time tosave data and system that is less update related to information availability of room in the inpatient area soas to cause inpatient buildup in the hospitalization of admission patient. The Purpose of this research is toevaluate the SISIMIDU based on user satisfaction. This type of research is qualitative research with datacollection through questionnaires. Method used is the End User Computing Satisfaction the methodconsisting aspects of content,aspects of accuracy, aspects of the format, aspects of timeliness and aspectof ease of use. Result of the research of the five aspects, among others, the aspect of content 67%respondents expressed satisfaction, aspect of accuracy 100% respondents expressed dissatisfied, aspectsof format 67% of respondents expressed dissatisfied, the aspect of timeliness 100% of respondentsexpressed dissatisfied and aspect of ease of use 100% expressed dissatisfied. It is hoped that hospitals canmake improvements and development against SISMIDU in order for SISMIDU to provide information thatsuits the needs of the user.